Trace Elements in Native Sulfur as Indicator of Substance Sources in Fumaroles of Active Volcanic Regions (Ebeco Volcano, Paramushir Island) - Bortnikova S.B.; Bessonova E.P.; Kotenko T. (My University, 2010)
Information about trace elements in native sulfur is hardly accessible in scientific literature because of complexity of sulfur preparation analysis. Few available data are relied on semiquantitative spectral analyses. At the same time, composition of native sulfur on volcanoes is an important indicator of volatile transport of elements and can serve as a basis for modeling of volcanic system.
Keywords: Эбеко